2019
DOI: 10.3892/or.2019.7332
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between ANLN and KDR are prognostic for breast cancer survival

Abstract: Single nucleotide polymorphisms (SNPs) are the most common genetic variation in mammalian cells with prognostic potential. Anillin-actin binding protein (ANLN) has been identified as being involved in PI3K/PTEN signaling, which is critical in cell life/death control, and kinase insert domain receptor (KDR) encodes a key receptor mediating the cancer angiogenesis/metastasis switch. Knowledge of the intrinsic connections between PI3K/PTEN and KDR signaling, which represent two critical transitions in carcinogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…25 Surveys such as that conducted by Dai et al show that ANLN down-regulation takes part in the prognostic of breast cancer survival by interacting with KDR. 26,27 ANLN overexpression leads to poor prognosis and poor clinical outcome to anthracycline-based chemotherapy in breast cancer patients. 15 In our study, we documented that the doxorubicin resistance in MDA-MB-231/ADM cells was significantly higher than that in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 Surveys such as that conducted by Dai et al show that ANLN down-regulation takes part in the prognostic of breast cancer survival by interacting with KDR. 26,27 ANLN overexpression leads to poor prognosis and poor clinical outcome to anthracycline-based chemotherapy in breast cancer patients. 15 In our study, we documented that the doxorubicin resistance in MDA-MB-231/ADM cells was significantly higher than that in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 was found to interact with ANLN [56,57], and it is indicated that ANLN mobility is directly or indirectly regulated by CDK1 via phosphorylation [58]. The ANLN-actin-binding protein has been identified as being involved in PI3K/PTEN signaling, which is critical in cell life/death control [59]. CITK was proven to be associated with the localization of F-actin and ANLN at the abscission sites [60].…”
Section: Other Binding Partnersmentioning
confidence: 99%
“…KDR: Kinase insert domain receptor (KDR) is a primary vascular endothelial growth factor receptor that encodes a crucial receptor regulating the cancer angiogenesis/metastasis switch [59].…”
Section: Other Binding Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Anillin has attracted increasing attention as a potential disease-related gene (ORPH:93213, OMIM:616027). Evidence point at anillin expression levels being associated with cell proliferation and migration disorders in cancer and kidney diseases [146][147][148][149] . Additional roles for this actin binding protein have been reported in nerve cell development 150,151 and dysregulation of Anillin has been implicated in central nervous system myelin disorders 152,153 .…”
Section: Discussionmentioning
confidence: 99%